Strategi Membaca Pada Pembelajaran Bahasa Indonesia Di Sekolah Dasar Kelas Tinggi - Falih Daffa; Namira Sazkia; Nurul Handini; Nurhaliza Ertays Siregar; Putri Puspitasari (Jurnal Bintang Pendidikan Indonesia, 2023)
Learning to read in elementary schools is considered very important. This is due to the fact that learning to read plays not only a role in improving a child's language skills, but not only the ability of that, namely to improve students in learning other subjects. However, the teaching of reading in elementary schools is still below standard and far from expectations. This is because the development of children's reading habits is still not the main emphasis in learning to read in elementary schools. In addition, learning to read is still considered monotonous and boring. Some educators continue to use this method ineffectively when teaching students to read. On the other hand, the instructor ignores the development of students' metacognitive skills through mastery of various reading methods. Students who are still considered to have relatively low reading skills are likely to be affected by this situation. This paper provides a number of alternative reading learning techniques that are expected to improve students' understanding of basic school reading, especially in the high grades.